STRATEGI DAN TAHAPAN KEMAS ULANG INFORMASI DALAM ERA NEW NORMAL DI UNIVERSITAS PGRI SILAMPARI LUBUK LINGGAU SUMATERA SELATAN - Nanda Yudisman, Septevan; Bidayah Sari, Siti (UIN Imam Bonjol Padang, 2022)
Information repackaging provides a change in the search for data and collections in a library even in the new normal era as it is today, so there are new challenges and strategies in repackaging information. new normal at the PGRI Silampari University Library, Lubuk Linggau, which must follow the demands of libraries that display and play the role of information dissemination services, cultural preservation, and carrying out activities that are beneficial to the social and intellectual life of the users. Information repackaging is a response to technological advances and the information explosion. This study uses a purposive sampling technique to determine the informants in this study. Purposive sampling technique is how to determine informants by selecting informants according to the criteria and needs of the authors in this study. The chosen librarian at Pgri Silampari University is a librarian who has completed a master's degree in library at Sunan Kali Jaga State Islamic University, Yogyakarta. Information repackaging activities are carried out as well as possible, it will be able to provide an economic impact and selling value for the library. When packing information, the librarian must pay attention to the language used, which must be simple, not too scientific, easy to understand, written concisely, clearly means, and presents an attractive packaging.